2007
DOI: 10.1080/14756360600988989
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosinase inhibitory effects and inhibition mechanisms of nobiletin and hesperidin from citrus peel crude extracts

Abstract: The inhibitory effects of nobiletin and hesperidin from citrus peel crude extracts on tyrosinase diphenolase activity have been evaluated. IC 50 of nobiletin and hesperidin were 1.49 mM and 16.08 mM, respectively and their inhibition mechanisms are competitive type with inhibition constant (K i ) 2.82 mM and noncompetitive type with K i 9.16 mM, respectively. Crude extracts from citrus peel (C. unshiu Marc.) were extracted with 95% ethanol and fractionated by petroleum ether (PCPE). The ethanol phase (ECPE) wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Likewise, 50 μ M hesperetin increased melanin content by over 80% in murine B16-F10 melanoma cells [46]. In contrast, other studies demonstrated that hesperidin did not affect melanin production in B16F10 murine melanoma cells [4749]. However, most of other studies showed that both citrus extract and hesperidin inhibited melanogenesis in both murine B16-F10 melanoma cells and human melanocytes [36, 44, 5053].…”
Section: Benefits Of Hesperidin For Cutaneous Functionsmentioning
confidence: 99%
“…Likewise, 50 μ M hesperetin increased melanin content by over 80% in murine B16-F10 melanoma cells [46]. In contrast, other studies demonstrated that hesperidin did not affect melanin production in B16F10 murine melanoma cells [4749]. However, most of other studies showed that both citrus extract and hesperidin inhibited melanogenesis in both murine B16-F10 melanoma cells and human melanocytes [36, 44, 5053].…”
Section: Benefits Of Hesperidin For Cutaneous Functionsmentioning
confidence: 99%
“…Origanum vulgare (whitening agent: origanoside, a glycosylated phenolic compound) and Scutelleria baicalensis (whitening agent: baicalein, a flavone) extracts, as well as Morus (containing chalcones and stilbenoids) and Citrus (containing flavones, flavanones, and flavanols) species extracts also display interesting whitening properties [12,14,15,19,[161][162][163][164][165][166][167]. It was proven that oral intake for one year of pro-anthocyanidin-rich extract from grape seeds (Vitis vinifera) reduced the hyperpigmentation of women suffering chloasma [43].…”
Section: State Of the Artmentioning
confidence: 99%
“…36 During the melanogenesis, the key enzyme is tyrosinase, which contains a binuclear copper cluster in the common mushroom (Agaricus bisporus) and in human malignant melanoma. 37 The tyrosinase inhibitory activities of RG and FRC are shown in Figure 1. The tyrosinase-inhibitory activity (IC 50 ) of FRG was 27.63 lg/mL, which is more potent compared with RG (34.14 lg/mL), (P < .05).…”
Section: Inhibitiory Activities Against Tyrosinase and Elastasementioning
confidence: 99%